2013
DOI: 10.1002/jcc.23228
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of ionization and one‐electron oxidation potentials of N‐heterocyclic compounds

Abstract: A number of density functionals was utilized to predict gas-phase adiabatic ionization potentials (IPs) for nitrogen-rich heterocyclic compounds. Various solvation models were applied to the calculation of difference in free energies of solvation of oxidized and reduced forms of heterocyclic compounds in acetonitrile (AN) for correct reproduction of their standard oxidation potentials. We developed generally applicable protocols that could successfully predict the gas-phase adiabatic ionization potentials of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…The parameters of the compounds in this study that characterize their ability to be reduced or oxidized are presented in Tables and 2. Despite the accuracy of the chosen computational method and according to our previous publications, we cannot expect the experimental accuracy in case of silica for the values of adsorption energy. Therefore, we presume that the parameters presented in Tables and 2 that characterize electron donor and acceptor properties of adsorbed species are not as accurate as in the case of gas phase or solution calculations.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The parameters of the compounds in this study that characterize their ability to be reduced or oxidized are presented in Tables and 2. Despite the accuracy of the chosen computational method and according to our previous publications, we cannot expect the experimental accuracy in case of silica for the values of adsorption energy. Therefore, we presume that the parameters presented in Tables and 2 that characterize electron donor and acceptor properties of adsorbed species are not as accurate as in the case of gas phase or solution calculations.…”
Section: Resultsmentioning
confidence: 87%
“…It has been previously shown that M05/tzvp density functional theory (DFT) augmented by inclusion of continuum model of hydration provides nearly experimental accuracy in the prediction of the values of redox potentials. [31,32] In this study, the same level of computational modeling is used for the prediction of redox potentials for nitrocompounds TNT, DNT, DNAN, and NTO, dissolved in water and adsorbed on a silica surface, taken here as the (001) surface of a-quartz. To determine whether the compounds in this study will be able to be reduced under natural conditions, we used a wide range of redox potentials which characterize the half-reaction in the iron system: Fe(II)/Fe(III) system and zero valence (metallic) iron Fe(0).…”
Section: Adsorption Has Similar Thermodynamic Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present scenario, the role of heterocyclic compounds as an organic linker is ubiquitous due to their strong metal coordination ability. Most of these heterocyclic compounds inherently exhibit tautomeric forms [12][13][14]. These tautomeric forms can provide versatile organic linkers for the design of an efficient MOF with desired pore size.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Vibrational analyses at the same level of theory were performed to confirm that all of the optimized structures correspond to be the local energy minima on the potential energy surfaces. Meanwhile, natural bond orbital (NBO) analysis 20 was carried out to investigate the trigger bond.…”
Section: Introductionmentioning
confidence: 99%